Study of clinical profile of acute kidney injury in medical intensive care unit in a tertiary care center: a prospective study - Taparia, Krishna; Paritekar, A. A.; Verma, Shashi K. (International Journal of Research in Medical Sciences, 2025)
Background: Acute kidney injury (AKI) is a condition characterized by a sudden decline in renal function, which can lead to long-term complications including chronic kidney disease and increased mortality. In critically ill patients, particularly in intensive care units (ICU), AKI poses a significant health burden. The aim of the study was to evaluate the clinical profile of AKI in the medical ICU of a tertiary care center. Methods: A prospective observational study was conducted over one year in the MICU of tertiary hospital. The study included 100 patients aged over 18 years, who developed AKI as per the acute kidney injury network (AKIN) criteria. Data on patient demographics, co-morbidities, clinical presentation, etiology, and treatment outcomes were recorded. Statistical analysis was performed using statistical package for the social sciences (SPSS) version 26.0. Results: The majority of patients (62%) were aged between 18-40 years, with a male predominance (64%). Sepsis (30%), snake bites (23%) and drug induced (19%) were the leading causes of AKI. Of the patients, 54% were diagnosed with stage 3 AKI, and 31% required renal replacement therapy (RRT). The mortality rate was 26%, with significant associations found between RRT requirement, hyperkalaemia, metabolic acidosis, and increased mortality. Conclusion: Sepsis especially pneumonia and snakebite were the predominant etiological factors for AKI. Comorbidities, stage of AKI, RRT, along with complications like hyperkaleamia and metabolic acidosis, are the key predictors of poor outcomes and higher mortality rate. This emphasizes the importance of early detection, effective management strategies and continuous monitoring to reduce mortality and improve patient outcomes in the ICU setting.